Perceptions of Sexual Abuse in Sport: A Qualitative Study in the Portuguese Sports Community - Joana Alexandre; Catarina Castro; Maria Gama; Patrícia Antunes (Frontiers Media S.A., 2022)
Child sexual abuse is a complex issue that can take place in different contexts. Sports settings have specific features which pose increased risk for sexual abuse to occur. Recently, a country-specific roadmap for effective child safeguarding in sport was launched. Considering the need to achieve a comprehensive picture of violence against children in sports settings in Portugal, we analyzed the perceptions of the sports community in Portugal regarding child sexual abuse, its victims and perpetrators, and the specific risk factors in sports settings, as studies about this specific topic are scarce at the national level. A descriptive exploratory study was conducted using an online questionnaire with open-ended questions. Three hundred participants, i.e., sports managers, coaches, and athletes over 18 years of age (M = 33.13; SD = 13.062), of which 55.7% were female, answered. A thematic analysis of these data was conducted using NVivo software. Inter-rater agreement was strong for almost all variables. Results indicated that sexual abuse is perceived as being associated with physical and emotional abusive behaviors for which there is no consent from the victim, in a relationship that is guided by a relationship with power imbalances. Victims were mainly perceived as being female children, and perpetrators as adult males in a powerful position over the victim. As to possible signs of sexual abuse victimization, results showed that the participants identify behaviors, such as isolation, and physical evidence, such as marks and injuries. Risk factors specific to sports setting included the physical contact involved in many modalities, as well as the close and trustful relationship established between coach and athlete. Results are in line with previous studies showing that coaches, athletes, and sports managers share a common understanding of sexual abuse, although not always accurate. These results shed light on important practical and policy implications relevant to country-specific sport policies for effectively safeguarding children.